(untitled) (Scientific journal of the Fergana State University, 2023)
The article discusses the monograph "Anvar Obidjon poetic world" published in Tashkent in 2022 by the publishing house "Yangi asr avlodi" of the Youth Coach of the Republic of Uzbekistan, Professor Yuldash Solijonov. The monograph analyzes the methodological features of the work of Anvar Abidjan, who worked effectively in a number of genres of poetry, poetry, drama, comedy, journalism, and made a worthy contribution to the renewal of children’s and adult literature. The author has made a great contribution to the Uzbek literature by studying the works of the multifaceted talent, and has been able to cover the aspects of his style and artistic skills, as well as his poetic world in different perspectives. Through the analysis of the works collected in the monograph in the books "Selected Poems" 1, 2 and "Selection" (they were published by "Sharq" in 2006, the next in "AKADEMNASHR" in 2017) the contribution to the development of Uzbek literature are enlightened.